THU0319 Overall safety of 7-week secukinumab exposure during pregnancy in women with psoriatic arthritis. (12th June 2018) - Meroni, M.; Generali, E.; Guidelli, G.M.; Parodi, M.; Cutolo, M.; Selmi, C.
Abstract : Background: Psoriatic arthritis (PsA) often affects women of reproductive age. Secukinumab (SEC), a monoclonal antibody against interleukin-17A is effective in contrasting the progression of articular and cutaneous manifestations of PsA but has not been extensively studied in pregnancy, despite 84 cases of accidental exposure reported with reassuring safety outcomes. Objectives: To evaluate the maternal and fetal outcomes in women with PsA exposed to SEC during pregnancy. Methods: During a 10 months observational period, we enrolled 6 patients, treated by SEC 150 mg subcutaneously every month after weekly induction. All of them stopped the treatment by the time pregnancy test turned positive. All women had previously been counselled about contraceptive methods adoption and the potential risk of becoming pregnant during SEC administration, signing an informed consent. We collected demographic and clinical data of both patients and babies, with a peculiar focus on maternal-fetal safety issues. APGAR scores at 1 min (APGAR1) and 5 min (APGAR5) from delivery were recorded. Results: We observed 6 pregnancies from 6 mothers (4 of European, 1 Asian and 1 Latin-American ethnicity). Patient mean age at conception was 336±131 months; disease duration, 62±27 months; pre-conceptional exposure, 46±9 weeks; the (estimated) post-conceptional exposure 7±2 weeks. No major gestational complications were reported. One mother consulted the Emergency Department for a syncopal episode, but after a routine evaluation and an observation of 6 hours, was discharged; her pregnancy was otherwise unremarkable. Four girls (mean weight: 3170±200 g) and 2 boys (mean weight: 3460±60) were born. Mean gestational age was 38±2 weeks; 3 vaginal deliveries (1 oxytocine-induced for scarce dilation) and 3 caesarean sections were observed. The APGAR scores were above 8, excepting for an APGAR1 of 6 (born with caesarean section), then turned on 10 at APGAR5. Results are summarised on table 1. DAPSA, for the whole population, was under 4 (remission) at conception, and remained stable after delivery. Conclusions: The present study, despite the limited number of observations, represents the first report on pre-conceptional exposure to SEC. The available data, due to the lack of controlled studies, place the drug's use on FDA "B" category. Of note, SEC failed to cause teratogenicity, when administered throughout the whole pregnancy in a study conducted on primates ( Cynomolgus monkeys). The limited knowledge on human beings suggests, nevertheless, not to administer SEC during pregnancy, unless a clear benefit overwhelm the potential risk. SEC, in conclusion, seems to have an acceptable safety profile, even when accidentally taken in the very first pregnancy phase. Reporting the cases of pregnancy exposures, as recommended by the ongoing Producer's policy, is the only way that would allow to confirm, or reject, this statement. A long-term follow-up of the mother and the offspring health, similarly, is needed. References: [1] Mouyis MA, et al. J Rheumatol2017;44:1. [2] Skorpen CG, et al. Ann Rheum Dis2016;75(5):795–810. [3] Warren R, et al. P2134 25th EADVC2016, Vienna (AUT). [4] Cosentyx® Core Data Sheet. Version 1.1. Disclosure of Interest: None declared